(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to explain the role of loan guarantee institutions in securing the repayment of loans, as the research problem crystallized around the fact that the guarantee is one of the legal procedures available to the bank in which the borrower undertakes to pay the loan value with interest, but this guarantee is no longer sufficient for the bank due to the possibility of non-payment risks. Which necessitates increasing the guarantees to allow securing payment, and the researcher chose a deliberate samplFrom (90) people surveyed in a sample of Iraqi private commercial banks (Trade Bay, Sumer, Mosul, Baghdad, Al-Ahly Al-Iraqi), and the researchers used the descriptive and statistical method to test the research hypothesis, and the results of the research showed that the research sample supports and greatly that the existence of a company To guarantee bank loans contribute to reducing the risk of non-payment of loans.